Effects of traditional Chinese medicine massage therapy on pain, functional activity, muscle activation patterns and proprioception in knee osteoarthritis: a randomised controlled trial protocol - Xin Zhou; Cheng Tang; Bowen Zhu; Yangyang Fu; Min Fang; Sitong Fang; Qingguang Zhu; Yuen Yee Janice Hiew (BMJ Open)
Introduction Health education, weight control and exercise therapy are recognised treatment options for the non-surgical management of knee osteoarthritis (KOA); however, the pain and muscle fatigue associated with exercise make it difficult for patients to initially adhere. Traditional Chinese medicine (TCM) massage is an important complementary and alternative therapy that can effectively address these deficiencies. According to TCM theory and preliminary clinical practice, loosening of the muscles while pointing to acupoints can promote the recovery of KOA. Therefore, we hypothesised that exercise therapy in conjunction with TCM massage may lead to more satisfactory results in terms of pain management, active functional muscle activation patterns and proprioception in patients with KOA.Methods and analysis A parallel, single-centre, randomised controlled trial involving 106 patients will be conducted at Shuguang Hospital, Shanghai University of Traditional Chinese Medicine. Eligible patients with KOA who agree to participate will be randomised via a 1:1 randomisation system into the experimental group (receiving TCM massage and exercise treatment) and the control group (receiving exercise treatment). The primary endpoint is the change in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for pain from baseline to 24 weeks. Secondary outcomes include knee function (measured using the WOMAC stiffness and WOMAC functional subscale questionnaire and the timed ‘Up and Go’ test), muscle activation states (evaluated with electromyography techniques), knee proprioception and treatment satisfaction, adherence, safety evaluation and other relevant factors. Outcome assessors and data analysts will be blinded to the allocations, and the participants will not disclose their specific allocations. Outcome analyses will be conducted on both intention-to-treat and per-protocol populations. A preliminary analysis will test whether TCM massage, in addition to exercise, has statistically better outcomes.Ethics and dissemination The study protocol has received approval from the Ethics Committee of Shuguang Hospital, Shanghai University of Traditional Chinese Medicine (2023-1357-124-01).All study participants will be required to give written informed consent. The findings of the study will be submitted to a peer-reviewed journal for publication and presented at scientific conferences. Additionally, the participants will receive copies of the results.Trial registration number ChiCTR2300077308.